NETFLIX & CHILL WITH MR. SOUL - Shamsul, Harbi; Hanisah, Kasbon (Pusat Bahasa Moden (PBM), 2022)
25 February 2022 – A total of 22 students from Sekolah Menengah Kebangsaan Indera Shahbandar (SMKIS) under Program Akademi Menara Gading Universiti Malaysia Pahang Yayasan Al-Sultan Abdullah 2021 (AMG UMP YASA) had a movie viewing reward to wrap up the 2021 school year. Hosted by Mr. Shamsul Harbi, they gathered at the Executive Lounge, UMP Pekan Library for a session of ‘Netflix & Chill with Mr. Soul’.